2011
DOI: 10.1128/jvi.00051-11
|View full text |Cite
|
Sign up to set email alerts
|

Canine Distemper Virus Matrix Protein Influences Particle Infectivity, Particle Composition, and Envelope Distribution in Polarized Epithelial Cells and Modulates Virulence

Abstract: In paramyxoviruses, the matrix (M) protein mediates the interaction between the envelope and internal proteins during particle assembly and egress. In measles virus (MeV), M mutations, such as those found in subacute sclerosing panencephalitis (SSPE) strains, and differences in vaccine and wild-type M proteins can affect the strength of interaction with the envelope glycoproteins, assembly efficiency, and spread. However, the contribution of the M protein to the replication and pathogenesis of the closely rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 39 publications
(55 reference statements)
1
12
0
Order By: Relevance
“…Despite their conserved role in assembly and budding, there are genus-and strain-specific differences between paramyxoviral matrix proteins that do not allow exchanging M proteins even between closely related viruses without affecting virus growth (36)(37)(38). In line with these studies, a recent crosscomplementation study by Yun et al (26) demonstrated that introduction of the Hendra virus M gene into NiV increased the replicative titers, likely as a result of an increased budding activity of HeV M.…”
Section: Discussionsupporting
confidence: 62%
“…Despite their conserved role in assembly and budding, there are genus-and strain-specific differences between paramyxoviral matrix proteins that do not allow exchanging M proteins even between closely related viruses without affecting virus growth (36)(37)(38). In line with these studies, a recent crosscomplementation study by Yun et al (26) demonstrated that introduction of the Hendra virus M gene into NiV increased the replicative titers, likely as a result of an increased budding activity of HeV M.…”
Section: Discussionsupporting
confidence: 62%
“…Late in infection, ongoing cell-to-cell fusion and virus replication cause extensive cytopathic effects and likely disrupt all basolateral trafficking pathways. The consecutive accumulation of the glycoproteins at apical surfaces might be triggered by an apical G/F retargeting promoted by the M protein, as proposed previously for other viruses (25,29,30,34,68,69). However, there is no evidence so far that G, F, and M meet and interact intracellularly before reaching the plasma membrane.…”
Section: Discussionmentioning
confidence: 75%
“…Envelope proteins can even be expressed at opposing membranes. Here, partial retargeting of the glycoproteins by the matrix protein to the site of budding is believed to be required for virus release (25,29,30,34,68,69). Resembling measles virus (29), NiV M, F, and G proteins possess opposing targeting signals.…”
Section: Discussionmentioning
confidence: 99%
“…Paramyxovirus HN/H/G and F protein cytoplasmic domains also contain tyrosine motifs, which result in transport of proteins to the basolateral surface of polarized cells (Runkler et al, 2009;Weise et al, 2010). These signals, however, are overridden by the homologous matrix (M) protein, resulting in direction of the glycoproteins to the appropriate cellular compartment for virus assembly (Dietzel et al, 2011;Naim et al, 2000).…”
Section: Introductionmentioning
confidence: 99%